Оптимизация управления производственными процессами хозяйствующих субъектов на основе парадигмы функционально-стоимостного анализа и функционально-стоимостного управления - Ходарева, О.А. (Економіка промисловості, 2012)
Здійснено пошук методів оптимізації управління виробничими процесами господарю-ючих суб'єктів. Сучасні господарюючі суб'єкти розглянуто як складні функціональні системи, що потребують відповідних підходів і методів оптимізації. Запропоновано можливість використання парадигми ФСА і ФСУ у вирішенні даної проблеми.
Ключові слова: виробництво, оптимізація, управління, система, процес, функція, метод. Осуществлен поиск методов оптимизации управления производственными процессами хозяйствующих субъектов. Современные хозяйствующие субъекты рассмотрены как сложные функциональные системы, нуждающиеся в соответствующих подходах и методах оптимизации. Предложена возможность использования парадигмы ФСА и ФСУ в решении данной проблемы.
Ключевые слова: производство, оптимизация, управление, система, процесс, функция, метод. At this time processes in production become complicated. Production needs to be developed and optimized. Optimization is a process of choosing the suitable solution from alternative ones. The manager may make mistakes in conditions where a complex analysis is needed becauseit is impossible to describe all complexity of many technological, organizational, social and economic functional communications in any system.
In this paper thesearchof methods to optimize process control business entities is realized. Modern business entities are considered as complex functional systems in need of the respective approaches and methods of optimization. The opportunity is offered to use the paradigm of FCA and FCM in solving this problem.
Keywords: production, optimization, management, system, process, function, method.